Reproductive and vegetative phenology of the micro endemic Stachytarpheta cassiae (Verbenaceae) - Guimarães, Gesline Ferreira; Soares, Michel Pereira; Santos, Renata Moreira dos; Santos, Fabíola Mendes dos; Ashworth, Lorena; Negreiros, Daniel; Aguilar, Ramiro; Fernandes, Geraldo Wilson (Rodriguésia, 2023)
Abstract The flora of the Brazilian rupestrian grasslands represents a hotspot of species richness and endemisms. Stachytarpheta cassiae (Verbenaceae), is a micro endemic species, from which nothing is known. Here, we quantified the activity and intensity of vegetative and reproductive phenophases throughout 12 months and tested for their seasonality and their relationship with local climatic variables. Both vegetative and reproductive phenophases were continuous. No seasonality was observed in the vegetative phenophases and none of them was influenced by climatic variables. Only flower buds and mature fruits’ intensities showed seasonality in February (rainy season) and July (dry season), respectively. Accordingly, increased temperature and humidity combined explained increased production of flower buds whereas decreased rainfall explained increased mature fruits. Higher intensity in flower buds may respond to similar climatic conditions as other species in the community. However, S. cassiae is much different as it continues producing flowers continuously. Higher intensity of mature fruits in the dry season is expected as their seeds are abiotically dispersed. Due to constant flower and leaf production, S. cassia may be a key species for the conservation of many vertebrate and invertebrate species and for maintaining the biogeochemical functioning of the impoverished soils of the rupestrian grasslands. Resumo A flora dos campos rupestres brasileiros representa um hotspot de riqueza de espécies e endemismos. Stachytarpheta cassiae (Verbenaceae) é uma espécie micro endêmica, da qual nada se sabe sobre sua história natural. Aqui, quantificamos ao longo de 12 meses a atividade e intensidade das fenofases vegetativas e reprodutivas e testamos sua sazonalidade e sua relação com as variáveis climáticas locais. Tanto as fenofases vegetativas quanto as reprodutivas foram continuas. Não foi observada nenhuma sazonalidade nas fases vegetativas e nenhuma delas foi influenciada por variáveis climáticas. Somente os botões florais e a intensidade de frutos maduros mostraram sazonalidade significativa em fevereiro (estação chuvosa) e julho (estação seca), respectivamente. Assim, o aumento da temperatura e umidade combinados explicaram o aumento da produção de botões florais, enquanto a diminuição da precipitação explicou o aumento dos frutos maduros. A maior intensidade dos botões florais pode responder a condições climáticas semelhantes às de outras espécies na comunidade. No entanto, S. cassiae é muito diferente, pois produz flores continuamente. É esperada maior intensidade de frutos maduros na estação seca, já que suas sementes são dispersas por vetores abióticos. Devido à produção constante de flores e folhas, S. cassia pode ser uma espécie chave para a conservação de muitas espécies de vertebrados e invertebrados e para a manutenção do funcionamento biogeoquímico dos solos empobrecidos dos campos rupestres.